Transabdominal and transvaginal repair of vesico-vaginal fistula with bovine pericardium (Tutopatch®). A double case report - Dario Del Biondo; Dante Di Domenico; Giorgio Napodano; Marco Grillo; Felice Crocetto; Biagio Barone (Urology Case Reports, 2025)
Vesico-vaginal fistula (VVF) is an abnormal connection between the bladder and vagina, usually occurring after complex oncologic gynecologic surgeries. It typically presents as continuous urinary incontinence and is diagnosed through clinical examination, imaging, and cystoscopy. Conservative management rarely achieves healing, making surgical repair the preferred option. We report two cases of VVF treated with Tutopatch®, a bovine pericardium-derived graft, used as an interposition graft via transabdominal and transvaginal approaches. Tutopatch® avoids the morbidity of autologous tissue harvesting and offers a feasible, safe, and effective alternative. It should be considered a valuable option in the surgical management of complex VVF.